Effect of M9, MM106 and Seedling Rootstocks on Sunburn-Sensitivity of 33 Apple Cultivars, and Sunburn Effects on Fruit Quality - Racskó, József; Thurzó, Sándor; Drén, Gábor (Acta Agraria Debreceniensis, 2005)
The purpose of this study was to investigate the sunburn-sensitivity of 33 apple cultivars grafted onto 3 rootstocks (M9, MM106 and seedling) in a commercial orchard at Nagykutas (in the western part of Hungary). The authors also searched for any relationship between fruit quality parameters and the frequency of sunburn on the fruit surface.During the observations, the cultivars had rootstock-specific properties in respect to sunburn-susceptibility. Accordingly, the injury decreased in the order M9, MM106 and seedling rootstocks. The differences in the sensitivity were founded on the foliage-morphological characteristics of trees, caused by the growing vigour of the rootstocks. Accordingly, the highest value of sunburn injury was observed on M9 rootstock, because this rootstock has a dwarfing effect on the grafted main cultivars. Thus, the vegetative area of these trees grew very slowly and the foliage was not compact enough to protect the fruits from the strong rays. The largeness and density of the foliage increased in the order M9, MM106 and seedling rootstocks. Relationships were also demonstrated between the diameter of the upper part of crown, the size of leaves, the number of fruits per tree and the injury from sunburn.The damage values showed, that the gravity of symptoms did not decrease below a well-defined level of dimension on fruit. Determined potential area of injury was necessary for the symptoms to become visible.The authors categorized the cultivars in the respect of values of sunburn frequency: I. „Not sensitive”, II. „Moderately sensitive” and III. „Very sensitive” categories were constituted. Generally, the Gala cultivars showed low damage (or were free of symptoms), in contrast, Golden mutants suffered relative strongly. The most sensitive cultivar was Jonica on all three of rootstocks.We searched for any relationship between the fruit quality parameters and the frequency of sunburn. A significant correlation was found in the cases of fruit weight and colour-coverage. The latter can be related to that fact that highly colour covered fruits are found on the peripherial part of crown, so these are exposed to stronger sun rays